ANALISIS POTENSI, TANTANGAN, DAN PROSPEK PENGEMBANGAN WISATA HALAL BERBASIS PERSEPSI GENERASI Z DI KOTA PASURUAN - Nurul Rokhis Amelia; Aslikhah; Sukamto (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to analyze the potential, challenges, and prospects of halal tourism development based on Generation Z perceptions in Pasuruan City, particularly in the Pasuruan City Square as a public space with strategic value for Muslim-friendly tourism development. This research employs a qualitative approach with a phenomenological design to understand the subjective experiences and meanings of Generation Z regarding halal tourism. Data collection techniques include in-depth interviews with 10 informants selected through purposive sampling, supported by observation and documentation. Data analysis is conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings reveal that Pasuruan City Square has strong potential as a halal tourism destination based on public space through the integration of recreational, social, and religious functions, supported by pilgrimage activities, the availability of worship facilities, and good accessibility. However, its development still faces several challenges, including suboptimal facility quality, environmental cleanliness issues, inadequate spatial management, and the absence of formal halal standardization. On the other hand, the development prospects are highly promising, driven by Generation Z’s adaptability to technology and the significant influence of social media in shaping travel interest. Therefore, an integrated development strategy is required, including improving service quality, strengthening halal identity, and optimizing digital promotion.